THE SPECIFIC ROLE OF LIVER IN EXPELLING ANCYLOSTOMA CANINUM LARVAE FROM THE HOST SYSTEM - V. VIVEKA VARDHANI; G. SAKUNTHA (The Bioscan, 2011)
The present study was designed to understand the specific role of liver in the retention and migratory behavior of Ancylostoma caninum larvae in male Swiss albino mice. The larvae retention in liver was investigated in male mice infected orally with 500 (group A), 1000 (group B) and 2000 (group C) larvae /mouse. Larval migration in to liver occurred earlier (on day 1 of infection) in all the three groups (A, B and C) and a higher % of larvae migrated in to liver in group A (500 dose) then in groups B and C. interestingly, larvae did not stay in liver from day 9 to 30 in all the three groups.